External surface and pore mouth catalysis in hydrolysis of inulin over zeolites with different micropore topologies and mesoporosities. Issue 5 (14th February 2017) - Oh, Su Cheun; Nguyendo, Thien; He, Yao; Filie, Amanda; Wu, Yiqing; Tran, Dat T.; Lee, Ivan C.; Liu, Dongxia
Abstract : External surface and pore mouth catalysis for inulin hydrolysis over zeolite catalysts. Abstract : Hydrolysis of inulin over zeolite catalysts with various micropore topologies (FER, MFI, MOR, BEA, MWW and FAU) and mesoporosities (pillared MFI (PMFI) and pillared MWW (PMWW)) was studied. The reaction includes cleavage of four types of glycosidic bonds: the terminal glucosyl to fructosyl bond to produce glucose, the terminal sucrosyl to fructosyl bond to form sucrose, and the terminal fructosyl to fructosyl bond and internal fructosyl bonds within the polymer chain to generate fructose. Inulin conversion has shown an initially slow rate followed by pseudo first-order kinetics. Fructose production occurred at a much faster rate than that of sucrose followed by glucose. Rigorous kinetic data analysis showed that the reaction was inclined to proceed on the external surface acid sites of zeolites with cleavage of terminal sucrosyl to fructosyl and terminal fructosyl to fructosyl bonds. The increase in the micropore size in zeolites promoted pore mouth catalysis for the cleavage of the terminal fructosyl to fructosyl bond and terminal glucosyl to fructosyl bond. The mesoporosity in PMFI and PMWW zeolites enhanced external surface and pore mouth catalysis compared to those of their microporous analogues, but did not enable new types of catalytic events. The measured kinetic data were interpreted using a mathematical model based on a network involving parallel and series reactions. Inulin hydrolysis was probed in the transition from external surface to pore mouth catalysis depending on the zeolite topology and mesoporosity in bulky biomass processing. The present study provides guidelines for the utilization of zeolites with variable topologies and porosities for processing inulin and other biomass feedstocks for food and energy applications.